The Federal System in Libya: Motives for Its Adoption and Reasons for Its Abolition (1951–1963). - Salimah Aboulkhayr Ahmed (Journal of Libyan Academy Bani Walid, 2025)
This paper discusses the historical and political circumstances that accompanied the establishment of the Libyan state after its independence in 1951 and the choice of a federal system among the three regions. It explains how geographical, social, and tribal factors made federalism an appropriate option at the beginning. It also examines the constitutional crises، the disputes between the federal government and the regional governments، and the influence of the royal court on political stability. The paper highlights the high financial costs of the federal system and the role of oil discovery in pushing toward a more centralized form of government. Finally, it shows how the federal system was abolished in 1963 and replaced with a unified state.